The Microstructure of Zr/Nb Nanoscale Multilayer Coatings Irradiated with Helium Ions; Coatings; Vol. 13, iss. 1 - Laptev R. S. Roman Sergeevich; Stepanova E. N. Ekaterina Nikolaevna; Pushilina N. S. Natalia Sergeevna; Kashkarov E. B. Egor Borisovich; Krotkevich D. G. Dmitry Georgievich; Lomygin A. D. Anton Dmitrievich; Sidorin A. A. Aleksey Anatoljevich; Orlov O. I. Oleg Igorevich; Uglov V. V. Vladimir Vasiljevich (2023, 2023)
Title screen